Reliability and psychometric properties of the religious attitude questionnaire in student population - F Rahmati Najarkolaei; MR Jafari; J Anisi; M Talkhabi (فصلنامه ابن سینا)
Abstract Background: Studies have shown that religiosity was protective factor in diseases and psychology disorders. Thus assessment of religious attitude among young population is important. This study aimed to evaluate the reliability and psychometric properties of a religious attitude questionnaire in order to produce an appropriate local instrument for measuring religious attitudes. Materials and methods: Totally, 428 new incoming students of Tehran University in 2011 were selected through quota and weighted sampling and answered 25 items religious attitude scale. In order to examine the construct validity, exploratory and confirmatory factor analysis was employed and Cronbach's alpha was used to examine the reliability. Results: The population was composed of 428 students with mean age of 23.2±5.1 years. The majority of them were single (%91) and unemployed (%81.1), and coming from township (%60). The descriptive statistics of the exploratory and confirmatory factor analysis indicate three factors with %65 of the variance and 0.96 of Kaiser-Meyer-Olkin (KMO) index. The components included religion as a supporting factor in life, religion as an internal need, and secularity. These components were approved by the exploratory and confirmatory factor analysis. The reliability of the questionnaire was measured at 0.94 using Cronbach's alpha. Conclusion: Meanwhile the validity and reliability questionnaire indices have been reported as a desirable level, this 25-questioned religious attitude questionnaire is a reliable and valid instrument that can be used for measuring religious attitudes.